Development of the Leisure Activity Participation Scale (LAPS). Issue 1 (2nd January 2020) - Yıldırım Şimşek, Kerem; Çevik, Hüseyin
Abstract : The purpose of the study was to identify key structures associated with leisure activity participation and develop a valid and reliable scale to measure leisure activity participation. The dimensions related to leisure activity participation were determined as a result of a literature review and focus group. Research data from two different samples were interpreted by exploratory factor analysis ( n = 243) and confirmatory factor analysis ( n = 336). Analysis results revealed eight dimensions related to leisure activity participation: relaxing, developmental, socializing, activity with an attractive environment, productive, esthetic, entertaining, and exciting activity. The validity of the scale was evaluated by content, convergent, and discriminant validity tests. Internal consistency and stability were tested through Cronbach's alpha and Pearson correlation coefficients. It was concluded that a valid and reliable measuring instrument had been developed.